Intercultural Communication Competence among Indonesian Pre-Service Teachers: a Quantitative Study - Idris, Mas Muhammad; Ningsih, Masnia (SUAR BETANG, 2025)
The concept of intercultural communication competence (ICC) has become increasingly important in both formal and informal language learning contexts. ICC refers to the ability to communicate effectively with individuals from diverse cultural, linguistic, and normative backgrounds. Despite its significance, there is a gap in the literature regarding the assessment of ICC, particularly in the context of Indonesian teachers. The  aim of this study is to assess the level of ICC among pre-service teachers in Indonesia. The study involved 66 randomly selected participants from three Indonesian private universities. Data were collected using a valid and reliable questionnaire and analyzed through descriptive statistics and a one-way ANOVA test, with normality as a prerequisite. The results revealed that pre-service teachers exhibited a high level of ICC, with strong intercultural attitudes, knowledge, and skills. Furthermore, no significant differences were found based on the universities attended, indicating that the institution did not influence ICC levels. These findings underscore the importance of assessing ICC in pre-service teachers and suggest that they are well-equipped to engage with individuals from diverse backgrounds in language learning contexts. The study highlights the need for further exploration of ICC in educational settings.